Telaah Kritis Implementasi Syirkah Melalui Akad Musyarakah pada Koperasi Pondok Pesantren - Nur Awali Khoirunnisa; Nuris Sirrul Laily; Nadziratul Ulya (Jurnal Ilmiah Ekonomi Islam, 2022)
Islamic syaria teaches the procedure of muamalah in several forms of contracts, one of which is the musharaka contract. The practice of Muamalah-Musyarakah contracts was used in the Islamic financial institution of Al-Yasini Kopontrs. This study was conducted using descriptive analytical qualitative methods. The purpose of this study is to explain how the Musyarakah Treaty is implemented in Kopontren Al-Yasini. The results of this study show that Al Yasini Islamic Boarding School Cooperative is a company that is not oriented towards big profits, but still adheres to Sharia law and the values of Akhlaqul Karimah, so when applying for business contracts, Sharia law is used - the contract includes Mudaraba, Musyarakah and Ijarah, but in practice prefer Musharaka contracts. And when executing the Musyarakah contract itself, for profit sharing, the capital owner will get 70% and the manager will get 30%.